<span>(2p + q) ( –3q – 6p + 1)
= -6pq - 12p^2 + 2p - 3q^2 - 6pq + q
= -12p^2 -12pq +2p -3q^2 + q
so answer is b. </span> -12p^2 -12pq +2p -3q^2 + q
Answer:
A. (x-5)(x-5)
Step-by-step explanation:
We need to factor x^2-10x+25 into the form (x+y)(x+y) where 2y=-10 and y^2=25
2y=-10
y=-5
So this becomes (x-5)(x-5)
Hope this helped!
Remember these two combinations: logab=loga+logb, log(a/b)=loga-logb
3logx=logx^3
(1/2)log(x+2)=log(x+2)^(1/2)
2log(z-4)=log(z-4)^2
so the given expression can be combined into log{[(x^3)(z-4)^2]/(x+2)^(1/2)}
Answer:
5/4 or 1 . 1/4
Step-by-step explanation:
3/4 + 1/2 = 5/4 or 1 . 1/4
Answer:
Step-by-step explanation:
34 to the 4